Comparison of coagulation pretreatment of produced water from natural gas well by polyaluminium chloride and polyferric sulphate coagulants. Issue 10 (19th May 2017) - Zhai, Jun; Huang, Zejin; Rahaman, Md. Hasibur; Li, Yue; Mei, Longyue; Ma, Hongpu; Hu, Xuebin; Xiao, Haiwen; Luo, Zhiyong; Wang, Kunping
ABSTRACT: This study aimed to optimise coagulation pretreatment of the produced water (PW) collected from a natural gas field. Two coagulants, polyferric sulphate (PFS) and polyaluminium chloride (PACl), were applied separately for the organics, suspended solids (SS), and colour removal. Treatment performance at different coagulant dosages, initial pH values, stirring patterns, and the addition of cationic polyacrylamide (PAM) was investigated in jar tests. The optimal coagulation conditions were dosage of PACl 25 g/L or PFS 20 g/L with that of PAM 30 mg/L, initial pH of 11, and fast mixing of 1.5 min (for PACl) or 2 min (for PFS) at 250 rpm followed by slow mixing of 15 min at 50 rpm for both coagulants. PACl performed better than PFS to remove chemical oxygen demand (COD), total organic carbon (TOC), SS, and colour, and achieved a removal efficiency of 90.1%, 89.4%, 99.0%, and 99.9%, respectively, under the optimal condition; while PFS efficiency was 86.1%, 86.1%, 99.0%, and 98.2%, respectively. However, oil removal was higher in PFS coagulation compared to PACl and showed 98.9% and 95.3%, respectively. Biodegradability, ratio of the biological oxygen demand (five-day) (BOD5 )/COD, of the PW after pretreatment increased from 0.08 to 0.32 for PFS and 0.43 for PACl. Zeta potential ( Z -potential) analysis at the optimum coagulant dosage of PACl and PFS suggests that charge neutralisation was the predominant mechanism during coagulation. Better efficiency was observed at higher pH. The addition of PAM and starring pattern had a minor influence on the removal performance of both coagulants. The results suggest that PACl or PFS can be applied for the pretreatment of PW, which can provide substantial removal of carbon, oil, and colour, a necessary first step for subsequent main treatment units such as chemical oxidation or biological treatment.